ABC News/Washington Post Poll, February 2007 ([Verlag nicht ermittelbar], 2009)
This poll, fielded February 22-25, 2007, is a part of continuing series of monthly polls that solicit public opinion on various political and social issues. A national sample of 1,082 adults was surveyed, including an oversample of African Americans, for a total of 157 African Americans respondents. Respondents were asked whether they approved of George W. Bush and the way he was handling the presidency and other issues such as the economy, whether they approved of the way Congress was handling its job, what was the most important problem they would like to see President Bush and Congress deal with, and whether they trusted Bush or the Democrats in Congress to do a better job handling issues such as health care and the federal budget. Opinions were solicited on Speaker of the House Nancy Pelosi, Secretary of State Condoleezza Rice, the 2008 presidential candidates, whom respondents would vote for if the 2008 Democratic and Republican primaries and the 2008 presidential election were being held that day, and whether they were more likely to vote for a candidate based on qualities such as religion, race, gender, or political interests. Respondents were asked how closely they were following the 2008 presidential race, what were the most important issues in their choices for Democratic and Republican candidates for president, and who they thought was most likely to win the Democratic and Republican nominations for president. Several questions asked about the war with Iraq, including whether the war with Iraq was worth fighting, whether United States military forces should remain in Iraq until civil order is restored there, whether there should be a deadline for withdrawing United States forces from Iraq, whether respondents were pleased with the way the Bush Administration was handling the war in Iraq, and whether respondents trust the Bush Administration to accurately report intelligence about possible threats from other countries. Additional questions asked about abortion, the war in Afghanistan, and Iran. Demographic information includes sex, age, race, education level, household income, religious preference, frequency of religious attendance, marital status, whether anyone in the household was a military veteran, whether anyone in the household was a member of a labor union, type of residential area (e.g., urban or rural), voter registration status, political party affiliation, political philosophy, and the presence of children under 18 in the household.